Peningkatan Kompetensi Siswa Kelas XII Keahlian Teknik Instalasi Tenaga Listrik Smk Negeri 1 Karawang Pada Mata Pelajaran Sistem Pengendali Elektronik Melalui Metode Kooperatif STAD - Widodo, Mugi (Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
This study aims to determine the effectiveness of the Student Team Achievement Division (STAD) technique of cooperative learning with the help of learning media Electronic Control System in improving the competency of class XII students in the expertise of Electrical Power Engineering in KARAWANG STATE VOCATIONAL SCHOOL on electronic control system subjects. This research is a classroom action research conducted in two cycles. Each cycle in this study consists of four stages of implementation, namely planning, action, observation, and reflection. Data collection was carried out using the instruments of affective observation sheets, psychomotor observation sheets, as well as pre-test and post-test instruments. The data analysis technique used is by reducing data, data exposure, and drawing conclusions. The results of the study showed an increase in student competence in the affective, psychomotor, and cognitive aspects after the implementation of the cooperative learning method of the STAD technique with the help of learning media Electronic Control Systems. In the affective aspect there was an increase of 48.21%, with the percentage of affective aspects of students in the first meeting amounting to 56%, increasing to 83% at the sixth meeting. In the psychomotor aspect there was an increase of 22.15%, with the psychomotor mean of students on job sheet 1 amounting to 67.66, increasing to 82.65 on job sheet 4. In the cognitive aspect there was an increase of 110.9%, with a value the average pre-test cycle 1 was 38.53, increasing to 81.26 in the post-test cycle 2.